Morphology and Structure of Electrolytically Synthesized Tin Dendritic Nanostructures - Nebojša D. Nikolić; Jelena D. Lović; Vesna M. Maksimović; Predrag M. Živković (Metals, 2022)
The formation of tin dendritic nanostructures by electrolysis from the alkaline electrolyte has been investigated. Morphology and structure of Sn dendrites produced applying both potentiostatic and galvanostatic regimes of the electrolysis are characterized by SEM and XRD, respectively. Depending on the applied cathodic potentials, three types of Sn dendrites were obtained: (a) needle-like and spear-like, (b) fern-like, and (c) stem-like dendrites. The very branchy dendrites with branches of the prismatic shape obtained by the galvanostatic regime of electrolysis represented a novel type of Sn dendrites, not previously reported in the literature. To explain the formation of various dendritic forms, correlation with the polarization characteristics for this electrodeposition system is considered. The needle-like and the spear-like dendrites represented monocrystals of (200),(400) preferred orientation, the fern-like dendrites exhibited the predominant (220),(440) preferred orientation, while in the stem-like particles Sn crystallites were oriented to a greater extent in the (440) crystal plane than in other planes. The galvanostatically synthesized Sn particles possessed the strong (200),(400) preferred orientation. The strong influence of parameters and regimes of electrodeposition on structural characteristics of Sn dendrites is explained by the fundamental laws of electrocrystallization taking into consideration the concept of slow-growing and fast-growing crystal planes.